Swarm intelligence principles, advances, and applications - Hassanien, Aboul Ella; Emary, Eid (CRC Press, Taylor & Francis Group, 2016)
"Presents a comprehensive treatment of modern swarm intelligence optimization methods, complete with illustraive examples and an extendable MATLAB package for feature selection in wrapper mode applied on different data sets with benchmarking using different evaluation criteria. The book provides beginners with a solid foundation of swarm intelligence fundamentals, and offer experts valuable insight into new directions and hybridizations"--Back cover